Intestinal barrier permeability: the influence of gut microbiota, nutrition, and exercise - Dmytriv, Tetiana R.; Storey, Kenneth B.; Lushchak, Volodymyr I. (Frontiers in Physiology, 2024)
The intestinal wall is a selectively permeable barrier between the content of the intestinal lumen and the internal environment of the body. Disturbances of intestinal wall permeability can potentially lead to unwanted activation of the enteric immune system due to excessive contact with gut microbiota and its components, and the development of endotoxemia, when the level of bacterial lipopolysaccharides increases in the blood, causing chronic low-intensity inflammation. In this review, the following aspects are covered: the structure of the intestinal wall barrier; the influence of the gut microbiota on the permeability of the intestinal wall via the regulation of functioning of tight junction proteins, synthesis/degradation of mucus and antioxidant effects; the molecular mechanisms of activation of the pro-inflammatory response caused by bacterial invasion through the TLR4induced TIRAP/MyD88 and TRAM/TRIF signaling cascades; the influence of nutrition on intestinal permeability, and the influence of exercise with an emphasis on exercise-induced heat stress and hypoxia. Overall, this review provides some insight into how to prevent excessive intestinal barrier permeability and the associated inflammatory processes involved in many if not most pathologies. Some diets and physical exercise are supposed to be nonpharmacological approaches to maintain the integrity of intestinal barrier function and provide its efficient operation. However, at an early age, the increased intestinal permeability has a hormetic effect and contributes to the development of the immune system.